An analysis of the costs and quality of infrastructure facilities in informal settlements in Kumasi, Ghana. Issue 4 (2nd October 2018) - Gaisie, Eric; Poku-Boansi, Michael; Adarkwa, Kwasi Kwafo
ABSTRACT: The literature on urban development generally posits that informal settlements offer low cost housing to the urban poor in developing countries. Using data from four informal settlements in Kumasi, Ghana, this paper analyses the costs and quality of water and sanitation infrastructure delivery in relation to the socio-economic conditions of residents. It finds a paradox where residents of deprived informal settlements pay higher fees for the use of low-quality privately-owned outdoor commercial water and sanitation facilities. The study therefore calls for a re-examination of urban upgrading programmes to focus on approaches that consider the financial implications of projects on beneficiaries.